2011
DOI: 10.3390/s110201328
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Paste Electrodes Made from Different Carbonaceous Materials: Application in the Study of Antioxidants

Abstract: This work describes the sensing properties of carbon paste electrodes (CPEs) prepared from three different types of carbonaceous materials: graphite, carbon microspheres and carbon nanotubes. The electrochemical responses towards antioxidants including vanillic acid, catechol, gallic acid, l-ascorbic acid and l-glutathione have been analyzed and compared. It has been demonstrated that the electrodes based on carbon microspheres show the best performances in terms of kinetics and stability, whereas G-CPEs prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 33 publications
3
53
0
2
Order By: Relevance
“…One class of these materials are nanostructured carbonaceous materials, such as mesoporous carbon, carbon nanofibers, carbon nanotubes, and graphene. 14 Graphene is a material used in various fields due to its unique structural, mechanical, and electronic properties. 15 One important application of graphene is biosensing and electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…One class of these materials are nanostructured carbonaceous materials, such as mesoporous carbon, carbon nanofibers, carbon nanotubes, and graphene. 14 Graphene is a material used in various fields due to its unique structural, mechanical, and electronic properties. 15 One important application of graphene is biosensing and electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodes made using carbon microspheres were the most stable (giving consistent results for successive measurement of catechol, with a relative standard deviation of just 3.2%) and gave the best performances in terms of kinetics. Their work also demonstrated that an array combining the three electrode types could discriminate between a number of anti-oxidants depending on their chemical structure and reactivity [193].…”
Section: Stabilitymentioning
confidence: 99%
“…Carbon paste electrode (CPE) is a composite electrode constructed using carbon materials such as graphite (classical carbon paste electrodes), carbon nanotubes (carbon nanotube paste electrodes, CNPE), or derivates from the combination of two or more materials. CNPE consists of a homogeneous mixture of carbon nanotubes and a hydrophobic organic liquid (mineral oil, paraffin oil, or silicone oil) placed on a glass or plastic tube of diameter and depth defined [73,74]. Inam et al [75] detected the methiocarb insecticide by square-wave voltammetry (SWV) using a multi-walled carbon nanotube paste electrode.…”
Section: Carbon Nanotubes Sensorsmentioning
confidence: 99%